2015
DOI: 10.1108/ijhma-04-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the price of housing in Indonesia

Abstract: Purpose – This study aims to address the factors or attributes that would influence the price of residential products in Jakarta Metropolitan Region. Design/methodology/approach – In total, 202 respondents from all across Jakarta Metropolitan Region participated in the questionnaire for this study. Demographic questions are categorized into age, gender and preferences for real estate locations. The questionnaire was made based on the aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 39 publications
4
74
0
6
Order By: Relevance
“…Research on housing preferences has been developing over the last few decades (Rahadi et al, 2015b) where researchers have sought to investigate the topic from different theoretical perspectives and using various methodologies (Coolen & Hoesktra, 2001). For example, researchers have focused on examining consumer preferences for particular housing attributes/characteristics (Opoku & Abdul-Muhmin, 2010) and satisfaction with current housing situation (Djebarni & Abed, 2000;Tan, 2012b).…”
Section: Consumer Preferences For Housing Attributesmentioning
confidence: 99%
See 3 more Smart Citations
“…Research on housing preferences has been developing over the last few decades (Rahadi et al, 2015b) where researchers have sought to investigate the topic from different theoretical perspectives and using various methodologies (Coolen & Hoesktra, 2001). For example, researchers have focused on examining consumer preferences for particular housing attributes/characteristics (Opoku & Abdul-Muhmin, 2010) and satisfaction with current housing situation (Djebarni & Abed, 2000;Tan, 2012b).…”
Section: Consumer Preferences For Housing Attributesmentioning
confidence: 99%
“…For example, researchers have focused on examining consumer preferences for particular housing attributes/characteristics (Opoku & Abdul-Muhmin, 2010) and satisfaction with current housing situation (Djebarni & Abed, 2000;Tan, 2012b). Others have investigated issues such as the role of demographics, socioeconomics and values in influencing housing preference (Coolen & Hoesktra, 2001;Rossi & Weber, 1996) and the relationship between housing preferences and house prices (Rahadi et al, 2015b). Studies of housing preferences can also be divided into studies on stated preferences and those on revealed preferences (Coolen and Hoekstra, 2001).…”
Section: Consumer Preferences For Housing Attributesmentioning
confidence: 99%
See 2 more Smart Citations
“…In his research Rahadi, et al [14] divide these factors into three main groups, there are physical condition, concept and location. Physical conditions are properties possessed by a house that www.ijacsa.thesai.org can be observed by human senses, including the size of the house, the number of bedrooms, the availability of kitchen and garage, the availability of the garden, the area of land and buildings, and the age of the house [15], while the concept is an idea offered by developers who can attract potential buyers, for example, the concept of a minimalist home, healthy and green environment, and elite environment.…”
Section: A House Price Affecting Factorsmentioning
confidence: 99%